Sosialisasi Submit Jurnal Online Untuk Dosen Akademi Maritim Nusantara Banjarmasin - Galih Perdana; Noor Fathulliansyah (BALANTING Jurnal Pengabdian kepada Masyarakat, 2023)
Abstract The socialization includes an examination of the cultural environment of the social environment of the community concerned, social interaction and social behavior, with community service this time socializing online journal subitems with several submission stages is the initial stage of the publication process of various scientific journals. After the submit process is complete or successfully carried out, all that remains is to wait for the journal publisher's review process. Online can be done anytime and anywhere because online on the internet does not have time and age restrictions so that everyone can access the internet comfortably. Techniques or stages of implementing community service in socializing the introduction of the world of Journals nationally by providing direct material by one of the Indonesian Volunteer Journals by Mr. Galih, to provide material and practice in submitting scientific journals. Community service regarding the socialization of online journal submissions for lecturers at the Maritime Nusantara Archipelago Banjarmasin, very much providing information or knowledge that is very useful for improving the try dharma of permanent lecturers at the AMNUS Banjarmasin campus, because recognizing an online journal submission, of course there must be direction from the Journal that handles either from editors or Journal managers who have been fostered. Thus, it will be more enthusiastic and useful to add independent journals according to knowledge and as a group with collaboration combined with the science of Shipping Commerce Management. Keywords: socialization, submit, journal